2019
DOI: 10.3389/fphys.2019.00916
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Interactions Between Low-Frequency Oscillations and Beat-to-Beat Variability of Celullar Ventricular Repolarization in Response to Sympathetic Stimulation: Implications for Arrhythmogenesis

Abstract: Background and Objectives: Enhanced beat-to-beat variability of ventricular repolarization (BVR) has been linked to arrhythmias and sudden cardiac death. Recent experimental studies on human left ventricular epicardial electrograms have shown that BVR closely interacts with low-frequency (LF) oscillations of activation recovery interval during sympathetic provocation. In this work human ventricular computational cell models are developed to reproduce the experimentally observed interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 74 publications
(145 reference statements)
2
29
0
1
Order By: Relevance
“…Those enhanced magnitudes may facilitate the occurrence of arrhythmic events that can act as triggers for arrhythmias and at the same time they may contribute to a more vulnerable substrate by increasing spatial repolarization inhomogeneities between regions being at different oscillating phases. This increased arrhythmia susceptibility associated with elevated LF oscillations of repolarization has been postulated by in silico studies (Pueyo et al, 2016;Sampedro-Puente et al, 2019) and confirmed by in vivo research on a CAVB dog model (Sprenkeler et al, 2019) as well as clinical studies in postinfarction patients. (Rizas et al, 2017).…”
Section: Increased Arrhythmic Risk As a Function Of The Time Lapse Anmentioning
confidence: 59%
See 4 more Smart Citations
“…Those enhanced magnitudes may facilitate the occurrence of arrhythmic events that can act as triggers for arrhythmias and at the same time they may contribute to a more vulnerable substrate by increasing spatial repolarization inhomogeneities between regions being at different oscillating phases. This increased arrhythmia susceptibility associated with elevated LF oscillations of repolarization has been postulated by in silico studies (Pueyo et al, 2016;Sampedro-Puente et al, 2019) and confirmed by in vivo research on a CAVB dog model (Sprenkeler et al, 2019) as well as clinical studies in postinfarction patients. (Rizas et al, 2017).…”
Section: Increased Arrhythmic Risk As a Function Of The Time Lapse Anmentioning
confidence: 59%
“…A modified version of the Xie et al (2013) β-adrenergic signaling model was used as a basis to describe phosphorylation levels of cellular protein kinase A (PKA) substrates, as described in Pueyo et al (2016) and Sampedro-Puente et al (2019). The Xie et al (2013) model represents an evolution from the Soltis and Saucerman (2010) signaling model in which I K s phosphorylation and dephosphorylation rate constants were updated to better match experimental observations reported in Liu et al (2012).…”
Section: Pka Phosphorylation Modelmentioning
confidence: 99%
See 3 more Smart Citations